ENTREPRENEUR CHALLENGES IN MEXICO - Vargas-Hernández, José (2016)
As the twentieth century there has been particular interest in studying and understanding the role of the entrepreneur in Mexico because the entrepreneur benefits the economy of a country this research project aims to identify the challenges and entrepreneurial profile in Mexico, by identifying personal, social and professional skills that promote entrepreneurship successfully.